Size-dependent effects of nanoplastics on structure and function of superoxide dismutase. (December 2022) - Wang, Yaoyue; Shi, Huijian; Li, Tao; Yu, Lei; Qi, Yuntao; Tian, Guang; He, Falin; Li, Xiangxiang; Sun, Ning; Liu, Rutao
Abstract: The ubiquitous existence of nano-plastics (NPs) has attracted widespread concern. Currently, the uptake of NPs by organisms and cells has been reported. However, knowledge about the interaction between NPs and protein is still limited, and there is a gap in research on the size-dependent toxicity of NPs toward protein. In this study, multi-spectroscopic techniques and enzyme activity determination were used to explore the structure and function changes of the main antioxidant enzyme superoxide dismutase (SOD), caused by the binding of NPs with different particle sizes. Results indicated NPs with different sizes can directly interact with SOD. NPs with smaller sizes result in looser skeletons of SOD, while the larger lead to tighter peptide chains. In addition, NPs can bind with SOD to form complexes, and the smaller the NPs are easier to be induced to coalesce by SOD. The surface curvature of 100 nm NPs was more conducive to varying the secondary structure of SOD. NPs of 100 nm and 500 nm can cause greater sensitization of SOD endogenous fluorescence, and increase the polarity around tyrosine residue. The enzyme activity assay further revealed the functional differences caused by the size-dependent effects of NPs. NPs of 100 nm and 20 nm induced a more significant change in SOD activity (increased by 20% and 8%, respectively), while NPs of 500 nm and 1000 nm had a little impact on it. Together, smaller NPs have a greater impact on the structure and function of SOD. This study revealed the size-dependent toxicity of NPs to protein, which provided a rationale for the necessary avoidance and substitution of NPs in engineering applications. Graphical abstract: Image 1 Highlights: Smaller NPs result in looser skeletons of SOD, while larger NPs result in tighter peptide chains. Smaller NPs are easier coalesced by SOD. Surface curvature of 100 nm NPs was more conducive to varying the secondary structure of SOD. Smaller NPs have a greater impact on the structure and function of SOD.